Answer:
![a.b = (1*0) + (-4*2) +(1*-2)= -10](https://img.qammunity.org/2021/formulas/mathematics/college/kxzwm4rawou3oqv3lqi60jgpafn44s8uoj.png)
And replacing we got:
![cos \theta = (-10)/(√(18) √(8))= -(10)/(√(144))= -(10)/(12)= -(5)/(6)](https://img.qammunity.org/2021/formulas/mathematics/college/mqle1xk0nwgn6qoxsx4kt73s6cccdmtc31.png)
And we can find the angle with the inverse cosine function and we got:
![\theta =cos^(-1) (-(5)/(6))= 146.44°](https://img.qammunity.org/2021/formulas/mathematics/college/2az9qngkyt6t6c2y7901llwpg6dnxrs2qx.png)
Explanation:
for this case we can use the following identity:
![cos \theta = (a.b)/(|a| |b|)](https://img.qammunity.org/2021/formulas/mathematics/college/xf3urnhqk67xrkcoxwk78kmfot2vsm6yg5.png)
We can begin finding the norm for each vector and we got:
![|a| =√((1)^2 +(-4)^2 +(1)^2)= √(18)](https://img.qammunity.org/2021/formulas/mathematics/college/t57trt2a7gymdh0sc7eekceybkk7qhb8xx.png)
![|b| =√((0)^2 +(2)^2 +(-2)^2)= √(8)](https://img.qammunity.org/2021/formulas/mathematics/college/9twgtpmc4lvrx2xcspayil5c6ou1lxwvki.png)
Now we can find the dot product and we got:
![a.b = (1*0) + (-4*2) +(1*-2)= -10](https://img.qammunity.org/2021/formulas/mathematics/college/kxzwm4rawou3oqv3lqi60jgpafn44s8uoj.png)
And replacing we got:
![cos \theta = (-10)/(√(18) √(8))= -(10)/(√(144))= -(10)/(12)= -(5)/(6)](https://img.qammunity.org/2021/formulas/mathematics/college/mqle1xk0nwgn6qoxsx4kt73s6cccdmtc31.png)
And we can find the angle with the inverse cosine function and we got:
![\theta =cos^(-1) (-(5)/(6))= 146.44°](https://img.qammunity.org/2021/formulas/mathematics/college/2az9qngkyt6t6c2y7901llwpg6dnxrs2qx.png)